Conectividade do setor de serviços entre os estados da Região Nordeste - Souza, Vagner Mota de (2023)
The connectivity of the service sector between the states in the Northeast region was analyzed using Diebold and Yilmaz's methodology (2009, 2012, 2014), based on data from PMS from January 2011 to October 2022. The methodology used allows verifying the spillover relationships of the PMS index variation to which the states are exposed and the direction of these relationships, as well as identifying the most and least influential states in the region. This empirical exercise contributes to the understanding of the region's dynamics, guides the isolated or integrated actions of state governments, and helps to understand the shocks of each state among its peers and in the Northeast region regarding the service sector. Therefore, it is a relevant element from the perspective of regional development.